2021
DOI: 10.29103/ekonomika.v10i1.4504
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Penanaman Modal Asing Dan Ekspor Terhadap Produk Domestik Bruto Sektor Industri Di Indonesia

Abstract: This study aims to determine the effect of foreign investment and exports on GDP in the industrial sector in Indonesia. The data used in this study are secondary data from 2010 to 2018. The data analysis method used in this research is multiple linear regression analysis. The results show that foreign investment and exports have a positive and significant effect on the GDP of the Indonesian industrial sectorKeywords:Gross Domestic Product, Foreign Investment, Export

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…However, in the short term, Indonesian exports have a negative and insignificant impact on GDP as the t-statistic value is smaller than the t-table value. These findings align with research suggesting that exports have a positive and significant impact on the GDP of the industrial sector in Indonesia (Harun & Sari, 2021). However, another study found that exports do not significantly influence economic growth in Indonesia due to the country's dependence on imports as raw materials (R. K. Putri, 2021).…”
Section: The Impact Of Indonesian Exports On Gross Domestic Productsupporting
confidence: 83%
See 1 more Smart Citation
“…However, in the short term, Indonesian exports have a negative and insignificant impact on GDP as the t-statistic value is smaller than the t-table value. These findings align with research suggesting that exports have a positive and significant impact on the GDP of the industrial sector in Indonesia (Harun & Sari, 2021). However, another study found that exports do not significantly influence economic growth in Indonesia due to the country's dependence on imports as raw materials (R. K. Putri, 2021).…”
Section: The Impact Of Indonesian Exports On Gross Domestic Productsupporting
confidence: 83%
“…Exports are part of total expenditures, impacting the level of GDP. Consequently, if exports decrease, GDP will also decline (Harun & Sari, 2021). Consumption (C), investment (I), government expenditure (G), exports (E), and imports (M) are variables influencing GDP.…”
Section: Introductionmentioning
confidence: 99%